Pengembangan Media Pop Up Book Berbasis Cerita Rakyat Tanjungbalai terhadap Kemampuan Membaca Pemahaman Siswa Kelas 4 SD - Tivany Ramadhani; Rina Devianty; Aufa Aufa (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This study is entitled “Development of Pop Up Book Media Based on Tanjungbalai Folktales to Improve Reading Comprehension Skills of 4th Grade Elementary School Students.” The study aims to design and develop Pop Up Book media based on Tanjungbalai folktales and to evaluate its validity, practicality, and effectiveness in enhancing the reading comprehension skills of 4th-grade students. The theoretical foundation emphasizes the importance of using engaging and contextual visual media to support students’ reading comprehension. The research employed a Research and Development (R&D) method with the ADDIE approach. Data were collected through observations, interviews, validation questionnaires from material experts, media experts, and language experts, as well as pre-tests and post-tests. The results showed that the Pop Up Book media was assessed as “very valid” by three validators, with an average score of 89.68%. Meanwhile, feedback from educators and students categorized the media as “very practical,” with an average score of 96.48%. The effectiveness of the media was demonstrated by an increase in students’ reading comprehension skills, with an N-Gain score of 0.93. It is recommended that teachers use Pop Up Book media as an engaging and contextual learning alternative. Future researchers are encouraged to develop similar media using folktales from other regions.